Associations Between Hormonal Biomarkers and Cognitive, Motor, and Language Developmental Status in Very Low Birth Weight Infants. Issue 5 (September 2017) - Cho, June; Holditch-Davis, Diane; Su, Xiaogang; Phillips, Vivien; Biasini, Fred; Carlo, Waldemar A.
Abstract : Background: Male infants are more prone to health problems and developmental delays than female infants. Objectives: On the basis of theories of gender differences in brain development and social relationships, we explored associations between testosterone and cortisol levels with infant cognitive, motor, and language development ("infant development") in very low birth weight (VLBW) infants, controlling for mother–infant interactions, characteristics of mothers and infants, and days of saliva collection after birth. Methods: A total of 62 mother–VLBW infant pairs were recruited from the newborn intensive care unit of a tertiary medical center in the Southeast United States. Data were collected through infant medical record review, biochemical measurement, observation of mother–infant interactions, and standard questionnaires. Infant development was assessed at 6 months corrected age (CA), and mother–infant interactions were observed at 3 and 6 months CA. Results: General linear regression with separate analyses for each infant gender showed that high testosterone levels were positively associated with language development of male infants after controlling for mother–infant interactions and other covariates, whereas high cortisol levels were negatively associated with motor development of female infants after controlling for mother–infant interactions. Conclusions: Steroid hormonal levels may well be more fundamental factors for assessing infant development than infant gender or mother–infant interactions at 6 months CA. Abstract : Supplemental digital content is available in the text.